When Life Hurts... On the Verge of Death - Rodrigues, Rute; Oliveira, AbÃlio (Richtmann Publishing, 2012)
In this study, anchored in the theory of social representations, we intended to ascertain the existence of risk-taking and selfharmbehaviours, as well as situations of imminent death, in a population of adolescents (boys and girls between 15 and 19). It was alsoour aim to understand how these behaviours might be associated to the social representations of life, death and to musical preferences.Our findings indicate that boys are the ones who tend to find themselves more often engaged in all of the three forms of endangerbehaviours. It is also among the adolescents between 17 and 19 years old that these situations are more common. A preference forfeminine pop is associated to self-harm behaviour and classic pop is linked to risk behaviour. Personal fulfilment seems to be thegreatest indicator of both risk behaviour and self harm: the lower the perception of fulfilment, the greater the chance to adopt these kindof behaviours. Results also support that negative perceptions of well-being, and love for life are linked to risk and self harm behaviours,mainly in girls. Adolescents who shown risk behaviours represented death as a ritual and so did girls who had already found themselveson the verge of dying.